Horticultural subsectors in Antigua, Barbados, Belize and Dominica (Stevenson & Kellog Management Consultants TorontoCA, 1980)
Describes the horticultural subsector in Antigua, Barbados, Belize and Dominica. For each subsector describes the institutional environment within which the hprticultural production, distribution and marketing systems operate. Also describes the production, marketing, handling and transporting, and processing of horticultural products.
Project report